Ḥarakāt Al-Ṭawā‘if al-Bāṭinīyah al-Indūnīsīyah qabla Indiwā’iha that Ri‘āyati al-Tarbīyah wa al-Thaqāfah - Alim, M. Ghufron Zainul (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
It is inevitable that the presence of Islam in the archipelago little more spark religious conflict in the region . Local people have been accustomed to living in a Hindu - Buddhist teachings systems for centuries . The influence of these religions not only revolves around the ritual affairs , but has its roots in various aspects of life . The establishment then faltered when Islam comes to offer a different concept of life . Through the history of data it can be seen how the Majapahit kingdom must bow to the Demak kingdom held by Muslims . Of course not all conflicts arise in the form of political infighting . Conflict between Hindu - Buddhist and Islam can also appear in literary expression . In those days , such as the writings appear Gatoloco Fiber or Fiber Darmogandul , which clearly indicates the existence of tensions or religious conflicts . The word